Strategi Sederhana Mengelola Aset Tetap bagi UMKM: Efisiensi dan Keberlanjutan Usaha - Ambarwati Akib (Jurnal Akuntansi Nommensen, 2026)
This study aims to analyze the management of fixed assets, depreciation, and asset impairment in Bob Tailor, a micro, small, and medium enterprise. This research employed a descriptive qualitative approach, with data collected through interviews and direct observation of the business owner. The findings show that Bob Tailor owns several fixed assets, including sewing machines, a fabric cutting machine, and work tables, all of which are directly used in daily operations. However, the recording of fixed assets remains simple and does not yet include acquisition cost, useful life, accumulated depreciation, or book value. The owner has not applied depreciation calculations because assets are still assessed mainly based on their physical usability. In addition, asset impairment is understood informally through declining functional quality and the emergence of newer sewing machine models. A depreciation simulation using the straight-line method indicates that depreciation recording can help present asset values more fairly. This study highlights the importance of simple fixed asset recording for MSMEs to improve financial information quality and support business sustainability.